Pelatihan Tata Hidangan bagi Masyarakat di Desa Kedonganan, Badung, Bali - Ni Kadek Eni Juniari; Putu Mira Astuti Pranadewi (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
Kedonganan Village is famous as a culinary tourism village. Developments and increasingly fierce competition, the village considers it necessary to prepare human resources who can provide maximum service to tourists. In response to this, training is needed on excellent service, hygiene, sanitation and work safety as well as the manufacture of mixed drinks for the community. The purpose of this activity is to provide an overview of the field of hospitality and service excellence to the community in Kedonganan Village, to provide an understanding of hygiene, sanitation and work safety as well as basic knowledge of beverages to the community in Kedonganan Village, as well as to provide training on how to making and serving mixed drinks for the community in Kedonganan Village. The participants of the activity were a total of 60 people, consisting of representatives from 6 Banjars in Kedonganan Village. This activity is carried out with 3 (three) methods, namely in the form of lectures, discussions and direct practice. The results of this activity can be seen from the enthusiasm of the participants in participating from the first day to the end and the participants gave very positive responses to this activity. They hope that such activities can be carried out continuously with different materials.